A extensão universitária na perspectiva da educação popular e suas contribuições para a formação dos estudantes da Universidade Federal da Paraíba: possibilidades e limites - Rodrigues, Janaina Lima Luna (2021)
The present work is about a proposal of Popular Extension of the Federal University of Paraíba. It aims to understand how the pedagogical actions and practices developed in the Project of Popular Education and Family Health Care (PEPASF), between 2016 and 2020, had repercussions on the training process of extension students, especially considering the environment of political polarization of such period, which has as a remarkable fact the deposition of President Dilma Rousseff. Some of the main analytical categories of the work are, for example, Popular Education, Popular Extension, dialogue, liberation and conscientization. From a methodological point of view, the study was operationalized by conducting semistructured interviews with six extension students from the Project. The empirical material was scrutinized according to the thematic-category content analysis technique. The treatment of the empirical material resulted in five final categories that guided the approach towards achieving the general objective. Among the findings, an ambivalence was found: while the project's contribution to the academic-professional and emancipatory training of the extension students was noted, there were also setbacks in the Project and gaps from the point of view of critical training in the period 2016-2020. This situation has been accentuated by the resonances of political polarization that have degraded Brazilian democracy in these years.